Emission of fine particles (PM2.5) from residential biomass combustion in Croatia and how to reduce it - Poljanac, Mirela (Array, 2020)
Wood burning in residential appliances is very represented in the Republic of Croatia. It is a main or an additional form of heating for many households in rural and urban areas and is therefore an important source of air pollution. The choice of energy and the combustion appliance used in home have a significant impact on PM2.5 emissions. The paper informs the reader about PM2.5 emissions, their main sources and impacts on human health, environment, climate, air quality, and the reason why PM2.5 emissions from residential wood burning are harmful. Paper also gives an overview of spatial PM2.5 emission distribution in Croatia, their five air quality zones and four agglomerations. The paper analyses the sources and their contribution to PM2.5 emissions with the relevance of PM2.5 emissions from residential plants, the use of fuels in residential plants and their contribution to PM2.5 emissions and PM2.5 emissions by fuel combustion technologies in residential sector. Appropriate strategies, policies, and actions to reduce the impact of residential biomass (wood) burning on the environment, air quality and human health are considered.